Sobre el valencià «gemecar» 'gemegar' - Veny, Joan (Caplletra. Revista Internacional de Filologia, 2002)
This paper focuses excusively on Valencian gemecar ‘gemegar’, “to whine”. It asserts that it is a generalized form in Valencian areas, where it can be found as early as the 15th century. On the one hand, it refutes the hypothesis that the word should be a back-formation from gemec, and on the other, that it should be linked to Mozarabic. The author shows the continuity with Aragonese gemecar, and underlines that Aragonese keeps intervocalic voiceless consonants, that gemecar can be found in Aragonese documents since the 14th century, and that it has expanded into neighbouring varieties, related to Aragonese (Murcian and Eastern Andalusian). Finally, the paper justifies the acceptance of the variety gemecar, alongside gemegar, in standardized Catalan.